In vitro release of metformin hydrochloride from sodium alginate/polyvinyl alcohol hydrogels. (2nd January 2017) - Martínez-Gómez, Fabián; Guerrero, Juan; Matsuhiro, Betty; Pavez, Jorge
Highlights: Sodium alginate (Mn 87.400 g/mol) (S. Alg) with definite composition was used. PH stimulus responsive S. Alg:PVA hydrogels were obtained by freeze-thaw cycles. 1:1 w/v S.Alg/PVA hydrogels presented 20 g/g swelling ratio in distilled water. 55% of metformin was released after 6 h at pH 8.0, from 1:1 w/v S.Alg/PVA hydrogel. Abstract: Hydrogels, based on polysaccharides have found a number of applications as drug delivery carriers. In this work, hydrogels of full characterized sodium alginate (Mn 87, 400 g/mol) and commercial poly(vinyl alcohol) (PVA) sensitive to pH and temperature stimuli were obtained using a simple, controlled, green, low cost method based on freeze-thaw cycles. Stable hydrogels of sodium alginate/PVA with 0.5:1.5 and 1.0:1.0 w/v concentrations showed very good swelling ratio values in distilled water (14 and 20 g/g, respectively). Encapsulation and release of metformin hydrochloride in hydrogels of 1.0:1.0 w/v sodium alginate/PVA was followed by UV spectroscopy. The hydrogel released a very low amount of metformin hydrochloride at pH 1.2; the highest release value (55%) was obtained after 6 h at pH 8.0. Also, the release of metformin hydrochloride was studied by 1 H NMR spectroscopy, the temporal evolution of methyl group signals of metformin showed 30% of drug release after 3 h.